PENGARUH NET PROFIT MARGIN, EARNING PER SHARE, RETURN ON EQUITY, DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BEI TAHUN 2016-2018 - Sutardi; Hada Aulia; Hedar Rusman; meslo Pardede (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2020)
Abstract:This study aims to examine the effect of Net Profit Margin, Earning per Share, Return onEquity, and Price to Book Value on stock prices in LQ-45 companies in 2016-2018. The method usedis quantitative methods. This study used SPSS version 25. The results partially explain that NetProfit Margin and Return on Equityhave a significant negative effect on stock prices, Earning perShare and Price to Book Value have a significant positive effect on stock prices. Meanwhile,simultaneously Net Profit Margin, Earning per Share, Return on Equity, and Price to Book Valuehave a significant effect on stock prices. Based on the calculation of the coefficient of determination,it shows that the stock price is influenced by the independent variables in this study of 81.5% and theremaining 18.5% is influenced by other variables outside of this study.Keywords: Stock Price, Net Profit Margin, Earning per Share, Return on Equity, and Price toBookValue